2019
DOI: 10.1002/dvdy.117
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled 4 regulates ventral blood vessel remodeling in the zebrafish retina

Abstract: Background Familial exudative vitreoretinopathy (FEVR) is a rare congenital disorder characterized by a lack of blood vessel growth to the periphery of the retina with secondary fibrovascular proliferation at the vascular‐avascular junction. These structurally abnormal vessels cause leakage and hemorrhage, while the fibroproliferative scarring results in retinal dragging, detachment and blindness. Mutations in the FZD4 gene represent one of the most common causes of FEVR. Methods A loss of function mutation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…[ 32 , 33 , [60] , [61] , [62] , [63] ]. Furthermore, vascular mural cell dropout has long been theorized to be a key player in microvascular homeostasis and recent studies have shown that loss of mural cells increases the susceptibility of the retinal vasculature to VEGF signaling and retinal angiogenesis [ 26 , [64] , [65] , [66] ]. Thus, the onset of retinopathy in aldh2.1 −/− larvae and adults was driven by an altered regulation of the MAPK family members and reduction of vascular mural cell coverage through the reactive metabolite AA independently of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 , 33 , [60] , [61] , [62] , [63] ]. Furthermore, vascular mural cell dropout has long been theorized to be a key player in microvascular homeostasis and recent studies have shown that loss of mural cells increases the susceptibility of the retinal vasculature to VEGF signaling and retinal angiogenesis [ 26 , [64] , [65] , [66] ]. Thus, the onset of retinopathy in aldh2.1 −/− larvae and adults was driven by an altered regulation of the MAPK family members and reduction of vascular mural cell coverage through the reactive metabolite AA independently of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of a N-terminal extracellular cysteine-rich domain, seven transmembrane domains, extracellular/intracellular loops, and a C-terminal intracellular domain [ 28 ]. Frizzled-4 plays the role of receptor to bind specific ligands, which is essential for initiating different signaling pathways, such as canonical Wnt/β-catenin pathway, planar cell polarity pathway, and Wnt/Ca 2+ pathway, this signaling pathway impairments could cause defective tissue homeostasis or cell proliferation in retina [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, to research the function of the frizzled4 gene, which is implicated in the development of familial exudative vitreoretinopathy (FEVR), one study found that pericytes in the zebrafish retina contain frizzled4 mRNA and have a very unique position on the retinal vasculature [80]. These observations could finally make the quantification of pericyte numbers in the zebrafish retina possible.…”
Section: Pericytesmentioning
confidence: 99%
“…However, as mentioned above, this marker cannot reliably stain pericytes on zebrafish retinal vessels. With the discussed transgenic reporter lines for vascular mural cells in zebrafish, and the recent confirmation of the morphology and localisation of pericytes in zebrafish [80], this should change in the future. Future research should elucidate how pericytes behave in diabetic or other pathological conditions in zebrafish, revealing more about their function and potentially making them a target for further research.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%